Critical thinking and contemporary mental health care: Michel Foucault's "history of the present". Issue 2 (11th November 2016) - Roberts, Marc
Abstract : In order to be able to provide informed, effective and responsive mental health care and to do so in an evidence‐based, collaborative and recovery‐focused way with those who use mental health services, there is a recognition of the need for mental health professionals to possess sophisticated critical thinking capabilities. This article will therefore propose that such capabilities can be productively situated within the context of the work of the French philosopher Michel Foucault, one of the most challenging, innovative and influential thinkers of the 20th century. However, rather than focusing exclusively upon the content of Foucault's work, it will be suggested that it is possible to discern a general methodological approach across that work, a methodological approach that he refers to as "the history of the present." In doing so, Foucault's history of the present can be understood as a productive, albeit provisional, framework in which to orientate the purpose and process of critical thinking for mental health professionals by emphasizing the need to both historicize and politicize the theoretical perspectives and therapeutic practices that characterize contemporary mental health care.